Peningkatan Skill Dibidang Multimedia Tingkat Sekolah Menengah Kejuruan - Marini, Marini; Sarwindah, Sarwindah; Yurindra, Yurindra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
Multimedia has entered an expertise program that is in great demand and has many opportunities in the 4.0th Industrial Revolution era because many companies need IT workers in the Multimedia field to introduce their companies and advance their businesses. The purpose of the test is to improve multimedia skills, to be able to master expertise in their area, not only to be able to work for companies but also to have a very important opportunity to create jobs or own a business. Mastery in designing multimedia products as well as mastery of techniques in making multimedia effects and creativity in presenting designed products. Themes in multimedia such as video making design, video editing, effects, moving animation in audio visual management, product design such as video formats, cover labels, DVDs and packing. The result of increasing expertise in the form of Video Design, Brochures is the achievement of the skills aspect consisting of preparation, implementation, design results.